2016
DOI: 10.1002/2016ja023333
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Van Allen Probes radiation belt proton data with test particle simulation for the 17 March 2015 storm

Abstract: The loss of protons in the outer part of the inner radiation belt (L = 2 to 3) during the 17 March 2015 geomagnetic storm was investigated using test particle simulations that follow full Lorentz trajectories with both magnetic and electric fields calculated from an empirical model. The simulation results presented here are compared with proton pitch angle measurements from the Van Allen Probe satellites Relativistic Electron Proton Telescope (REPT) instrument before and after the coronal mass ejection‐shock‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 18 publications
1
34
0
Order By: Relevance
“…Increased field-line curvature due to enhanced ring current during magnetic storms causes detrapping of protons for L ≳ 2 (Engel et al, 2015(Engel et al, , 2016. This is included in the trapped proton model with an approximate empirical estimate based on minimum storm time D st (Selesnick et al, 2013) and by the varying boundary condition at L = 2.4 that includes the effect of any losses at higher L. It should be more effective at higher E because of the larger gyroradius, but this is not accurately modeled and probably accounts for excess model proton intensity for E ≳ 50 MeV near L = 2 (Figure 3a).…”
Section: Field-line Curvature Scatteringmentioning
confidence: 99%
“…Increased field-line curvature due to enhanced ring current during magnetic storms causes detrapping of protons for L ≳ 2 (Engel et al, 2015(Engel et al, , 2016. This is included in the trapped proton model with an approximate empirical estimate based on minimum storm time D st (Selesnick et al, 2013) and by the varying boundary condition at L = 2.4 that includes the effect of any losses at higher L. It should be more effective at higher E because of the larger gyroradius, but this is not accurately modeled and probably accounts for excess model proton intensity for E ≳ 50 MeV near L = 2 (Figure 3a).…”
Section: Field-line Curvature Scatteringmentioning
confidence: 99%
“…The conservation of can be violated when the fields vary on the time scale of the gyroperiod or when the gyroradius ( ) is comparable to either of L, R c , or L s , the magnetic gradient, curvature, and shear scale lengths. The nonadiabatic motion of charged particles in highly curved magnetic fields has been previously studied (Birmingham, 1984;Buchner & Zelenyi, 1989;Chen, 1992;Chirkov, 1978;Hudson et al, 1997;Speiser, 1991;Young et al, 2002;Engel et al, 2016). Nonadiabatic motion of particles can also exist in sheared magnetic fields (Smets, 2000;Pfefferle et al, 2015) or for short scale length Northrop (1963).…”
Section: Chaotic Electron Motionmentioning
confidence: 99%
“…Until now, some satellite observations have shown that high‐energy protons in the inner radiation belt are relatively stable in comparison with electrons and low and medium energy ions in the inner and outer radiation belt. However, significant variations of high‐energy proton fluxes are observed in the outer boundary of the inner radiation belt ( L > 2.0), which are related to geomagnetic storms and solar energetic particle events (e.g., Engel et al, , ; Lorentzen et al, ; Selesnick et al, , ). The timescales of the variations in the high‐energy proton fluxes in the inner radiation belt caused by geomagnetic storms and solar proton events vary over timescales from days to years as summarized by Lorentzen et al ().…”
Section: Introductionmentioning
confidence: 99%